Lata Tebing Tinggi Selama, Perak: the ideal spot for a picnic & an appreciation of nature / Farhan Faat … [et al.] - Faat, Farhan; Mohamed Idris, Aida Khalida; Ahmad Ridzuan, Ahmad Hidayat; Salleh, Rashid (Faculty of Hotel & Tourism Management, UiTM Pulau Pinang, 2025)
Just imagine for a second a world where you may run away from it all and have fun in serene nature. Lata Tebing Tinggi in Selama, Perak is the kind of place where a picnic may turn into a fantastical day trip complete with roaring waterfalls, lush vegetation, and the enchanting sounds of the forest. Commuters' clamour fades into a serene setting as you approach Lata Tebing Tinggi. More and more breathtaking landscapes appear around every corner as the journey winds its way through the picturesque countryside. You can almost feel the lush sanctuary beckoning you as you approach the park gate, thanks to the soothing sound of trickling water. The brisk scent of the forest will greet you as you exit the car. You can feel the newness in the air. The picture perfect river glistens and calls out to you when the sun rays reach it. The soothing sound of the waterfall's trickle will put your body and soul to rest and rejuvenation.